PENGENALAN TEKNOLOGI RADAR UNTUK PEMETAAN SPASIAL DI KAWASAN TROPIS - Haniah, Haniah; Prasetyo, Yudo (Diponegoro University, 2011)
For tropical areas that often cloudy and experiencing rain, sensors based on optical satellite remote sensingoften encounter difficulties. This sensor is not able to optimally imaged region of interest due to clouds and rainobscured. Instead of wave-based sensor that uses microwave active sensors such as Radio Detection andRanging (RADAR) has advantages capable mencitra in various weather conditions, day and night, includingcoverage through the thick clouds and rain. Therefore, the radar system can help assess the level of physical andnon physical damage a wider area in quick time so that the scale of regional management priorities can bedetermined effectively and efficiently. Ability of SAR to penetrate clouds, covering the surface of the earth withtheir own signals, and can accurately measure distances, making the SAR is used for various applications, suchas: Monitoring of ice at sea, cartography, surface deformation detection, monitoring of glaciers, food cropproduction forecasting, mapping forest, ocean wave spectral, city planning, monitoring, disaster monitoring andshoreline